Too busy to care? Analysing the impact of system-related factors on maternal mortality in Zanzibar's Referral Hospital - Eline D. Veenstra; Tanneke Herklots; Khairat Said Mbarouk; Tarek Meguid; Arie Franx; Benoit Jacod (Taylor & Francis Group, 2022)
AbstractThis study analyses the contribution of system-related factors to maternal mortality in the low-resource setting of Mnazi Mmoja Hospital in Zanzibar, Tanzania. It is a retrospective cohort study including all maternal deaths (MD, n = 139) and maternal near-misses (MNM, n = 122) in Mnazi Mmoja Hospital with sufficient documentation during 2015 to 2018 (MD) and 2017 to 2018 (MNM). The number of admissions and surgical interventions per health care provider on the day of admission and the number of times vital signs were monitored per day were compared between MNM and MD cases using logistic regression. The mean number of times vital signs were monitored per day was associated with reduced odds of mortality (aOR 0.75, 95% CI 0.64-0.89), after adjustment for confounding factors such as severity of illness. The numbers of admissions or surgical procedures per health care provider were not associated with mortality. Concluding, the degree of monitoring of patients with life-threatening complications of pregnancy or childbirth is associated with the risk of mortality independent of the degree of severity. Preventing maternal mortality requires going beyond availability of essential interventions to tackle system-related factors that have a direct impact on the capacity to provide comprehensive care.Impact StatementWhat is already known on this subject? Root cause analyses of maternal deaths have identified many system-related factors, such as availability of health care providers, adequate training, and motivation to sustain high intensity monitoring (Madzimbamuto et al. 2014; Mahmood et al. 2018).What do the results of this study add? This is the first study to attempt to quantify the contribution of these system-related factors by comparing cases of maternal death with cases of maternal near-miss. We show that the degree of monitoring of patients with life-threatening complications is associated with the odds of mortality independent of the degree of severity. Even though this relation should not be regarded as causative, monitoring of vital signs can be seen as reflective of many system-related factors which hamper or facilitate comprehensive care.What are the implications of these findings for clinical practice and/or further research? This study helps increase general understanding of the factors leading to progression from severe disease to death in a high-volume low-income setting.